Research on the Coupling Coordination Relationship between Urbanization and the Air Environment: A Case Study of the Area of Wuhan - Ding, Lei; Zhao, Weituo; Huang, Yalin; Cheng, Shenggao; Liu, Chao (Atmosphere, 2015)
China’s high-speed socioeconomic development has been characterized by rapid urbanization and a series of ecological environment issues, especially air pollution. This paper proposed a comprehensive indicator system for the evaluation of urbanization and the air environment in Wuhan, a metropolis in central China, and then investigated the relationship between urbanization and the air environment from the perspective of coupling coordination theory. Furthermore, a coupling coordination degree model (CCDM) was constructed to estimate the relationship by using panel data collected from 1996–2013. The results showed the following: (1) Spatial urbanization and air environment quality make the greatest contributions to the compound system compared to other first grade indicators, indicating that they are critical factors to consider when the government is making relevant decisions about urban sprawl. (2) The comprehensive level of the air environment initially decreased from 1996–1998 and then increased with fluctuations in Wuhan, with several inflection points, meaning that the variation process of the air environment is unstable and repetitive, and efforts to improve the air environment must persist over a long period of time. Lastly, (3) the degree of coordinated coupling between urbanization and the air environment exhibited an S-shaped curve, indicating that Wuhan changed from having slightly unbalanced development to barely balanced development and then entered into a period of superiorly balanced development, with the air environment lagging. Thus, the ambient urban air quality has been subject to great pressure, and the government should continue to take effective action to improve it.